Investing in refugees: building human capital - Mottaghi, L (Refugee Studies Centre, University of Oxford, 2018)
Investing in refugees’ well-being is a global public good, and the international community should work to reduce malnutrition and increase access to education for refugees in order to help build human capital and achieve better economic outcomes for all.